Guiden till Spaniensverige Diaspora, integration och transnationalitet bland svenska föreningar i södra Spanien - Olsson, Erik (Anthropology & Society, 2018)
"""Guiden till Spaniensverige"" (The Guide to Spanish-Sweden) is an ethnographic account on the mobilisation of a social community of Swedish migrants who otherwise belongs to the diverse networks of lifestyle migrants or resident tourists in Southern Spain. The book is based on interviews with people who are engaged in Scandinavian associations/clubs or in other ways involved in practices which are associated with a Swedish community in Costa Blanca and Costa del Sol, which are two main destinations for lifestyle migrants in Spain. In addition the analysis is based on the discursive material that the social clubs, and to some extent other organisations and networks, are using in the service to their members. The book demonstrates how the practices of the large Scandinavian social clubs, but also other organisations like the Swedish church and some of the business associations, are operating at the locus of an ethnic and transnationalised form of community-making. The offering of a home-like social arena with social and cultural activities are privileging the Swedish language and the Swedish origin. This study concludes that the social practices employed by the clubs are guiding potential members to a social space in which preferably 'senior' Swedish migrants meet, socialise, and, to some extent, also consume in 'Swedish'. The book argues that the practices of the social clubs reveal the contours and infrastructure of a lifestyle diaspora in which a comfortable life in Spain - but in Swedish and with maintained relations with the Swedish society - is accentuated and given priority."